A Sandwich‐Shaped Hexanuclear Silver Complex with a Giant Cavity Constructed from a Macrocycle with Inward Chelating Units. Issue 4 (10th December 2020) - Nakamura, Takashi; Feng, Rui Yun; Nabeshima, Tatsuya
Abstract: The formation of a macrocyclic hexanuclear silver complex with a giant cavity (diameter ∼16.5 Å) is reported. Six silver centers are sandwiched by two molecules of a macrocyclic ligand possessing six pap (2‐[(pyridin‐2‐ylmethylene)amino]phenol) chelating units, and the metals are arranged on the wall of the internal cavity. Various analytical techniques revealed that each pap binds to the silver as an NN bidentate ligand. Abstract : The formation of a macrocyclic hexanuclear silver complex with a giant cavity is reported. Six silver centers are sandwiched by two molecules of a macrocyclic ligand possessing six pap (2‐[(pyridin‐2‐ylmethylene)amino]phenol) chelating units. Various analytical techniques revealed that each pap binds to the silver as an NN bidentate ligand.